The relationship between human resource practices and organizational commitment / Noorfariza Aliasad and Nur Adilah Ismail - Aliasad, Noorfariza; Ismail, Nur Adilah (2010)
Organizational commitment can be defined as the feeling of attachment and loyalty towards the organization. There are three forms of commitment; which are affective, continuance and normative. Organizational commitment can have a beneficial impact on organizations such as reduced turnover, lower absenteeism and increased productivity. The purpose of this study is to examine the relationship between the human resource practices (training, performance appraisal, reward system and staffing) and organizational commitment and to identify the most dominant human resource practices influence the organizational commitment and to identify the level of organizational commitment among the employees of Metro Specialist Hospital (MSH). This study gather data through questionnaire which contain organizational commitment and human resource practices measure. The questionnaires were distributed to a total of 169 respondents.